2016
DOI: 10.1377/hlthaff.2015.1632
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Expansion In 2014 Did Not Increase Emergency Department Use But Did Change Insurance Payer Mix

Abstract: In 2014 twenty-eight states and the District of Columbia had expanded Medicaid eligibility while federal and state-based Marketplaces in every state made subsidized private health insurance available to qualified individuals. As a result, about seventeen million previously uninsured Americans gained health insurance in 2014. Many policy makers had predicted that Medicaid expansion would lead to greatly increased use of hospital emergency departments (EDs). We examined the effect of insurance expansion on ED us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 25 publications
7
58
2
Order By: Relevance
“…Second, Medicaid enrollment was associated with significantly higher levels of ED use in sensitivity models that used entropy balancing. Our primary specification is consistent with prior work that indicated expansion of Medicaid was not associated with increased ED use, 36 but contrasts with findings from the OHIE which found higher levels of ED use after Medicaid enrollment. 17 A recent editorial on the issue noted, "the relationship between health insurance and emergency care isn't straightforward."…”
Section: Sensitivity Analysessupporting
confidence: 79%
“…Second, Medicaid enrollment was associated with significantly higher levels of ED use in sensitivity models that used entropy balancing. Our primary specification is consistent with prior work that indicated expansion of Medicaid was not associated with increased ED use, 36 but contrasts with findings from the OHIE which found higher levels of ED use after Medicaid enrollment. 17 A recent editorial on the issue noted, "the relationship between health insurance and emergency care isn't straightforward."…”
Section: Sensitivity Analysessupporting
confidence: 79%
“…Furthermore, the mean number of diversion hours by hospitals that declare diversions has remained high and has not changed significantly since 2007 (2007: 688 vs 2015: 683 hours, P = 0.96) . Finally, diversions will likely continue to be an issue both in California and nationally, given research that suggests that ED use and crowding did not decrease after Medicaid expansion and might have increased …”
Section: Discussionmentioning
confidence: 99%
“…Our data do not permit us to measure the number of patients, degree of crowding, physician and nurse staffing patterns, and number of ED boarders at the moment a hospital declares a diversion. However, it is unlikely that these factors disproportionately dictate the observation hospital's decision to divert when the neighboring hospital that diverted was public vs private, particularly because patient acuity does not vary depending on Finally, diversions will likely continue to be an issue both in California and nationally, given research that suggests that ED use and crowding did not decrease after Medicaid expansion36 and might have increased 37. Our findings are based on data from California and in metropolitan or urban areas, which may be different from other markets.Finally, our study design relies on matching nonsafety net hospitals by size and distance to safety net hospitals.…”
mentioning
confidence: 99%
“…Data that capture the direct effects of the ACA insurance coverage expansions on hospital utilization have been emerging. Studies using administrative data from the Healthcare Cost and Utilization Project (HCUP) found that Medicaid expansion led to shifts in payer mix from uninsured toward Medicaid for inpatient discharges and ED visits . Survey data from the National Health Interview Survey suggest increases in all‐payer inpatient utilization in Medicaid expansion states but no significant changes in ED utilization .…”
Section: Background and Research Objectivesmentioning
confidence: 99%
“…Studies using administrative data from the Healthcare Cost and Utilization Project (HCUP) found that Medicaid expansion led to shifts in payer mix from uninsured toward Medicaid for inpatient discharges 2,5 and ED visits. 6,7 Survey data from the National Health Interview Survey suggest increases in all-payer inpatient utilization in Medicaid expansion states but no significant changes in ED utilization. 8,9 A survey of lowincome adults in the 3 years following the ACA found better access to care, lower out-of-pocket spending, and improvements in preventive care for previously uninsured individuals gaining coverage.…”
Section: Review Of Recent Literaturementioning
confidence: 99%